THE INFLUENCE OF THE CEO POPULARITY ON PERFORMANCE OF BANKING COMPANIES AT THE EARLIER STAGES OF COVID-19 - Wardhani, Dian Kusuma; Supratiwi, Wiwik (UI Scholars Hub, 2021)
This study aims to obtain empirical evidence about the influence of CEO popularity on banking performance at the earlier stages of the COVID-19 pandemic in Indonesia. The CEO popularity significantly improve based on their achievements in the public mass media. The study sample consisted of 108 banking companies listed on the Indonesia Stock Exchange in Q1 - Q3 2020. Panel data regression with a common influence model approach was used for analysis, while the company performance was measured using Tobin's Q. The result showed that CEO popularity in the banking sector positively affects company performance. Therefore, hiring popular CEO helps obtain better company performance.